2016
DOI: 10.1111/pcmr.12454
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Leucocyte tyrosine kinase controls iridophore establishment, proliferation and survival

Abstract: The zebrafish striped pattern results from the interplay among three pigment cell types; black melanophores, yellow xanthophores and silvery iridophores, making it a valuable model to study pattern formation in vivo. It has been suggested that iridophore proliferation, dispersal and cell shape transitions play an important role during stripe formation; however, the underlying molecular mechanisms remain poorly understood. Using gain- and loss-of-function alleles of leucocyte tyrosine kinase (ltk) and a pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 59 publications
2
70
0
Order By: Relevance
“…To determine if leucophores or iridophores are involved in white stripe formation in A . ocellaris , we tested whether the drug TAE684 (TAE), known as an inhibitor of leukocyte tyrosine kinase (Ltk) and anaplastic lymphoma kinase (Alk) and leading to a decrease of iridophore number in zebrafish [31], could disrupt white stripe formation. Treatments with TAE at 0.6 μM or 0.3 μM during the metamorphosis of A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if leucophores or iridophores are involved in white stripe formation in A . ocellaris , we tested whether the drug TAE684 (TAE), known as an inhibitor of leukocyte tyrosine kinase (Ltk) and anaplastic lymphoma kinase (Alk) and leading to a decrease of iridophore number in zebrafish [31], could disrupt white stripe formation. Treatments with TAE at 0.6 μM or 0.3 μM during the metamorphosis of A .…”
Section: Resultsmentioning
confidence: 99%
“…TAE684 (NVP-TAE684) (HY-10192, MedChem Express), a specific inhibitor of Ltk and Alk [31], was diluted in dimethylsulphoxyde (DMSO; Sigma-Aldrich Louis, MI, USA) to a final concentration of 6 mM. Larvae were treated from 5 until 18 dph in 0.005% DMSO with 0.3 μM or 0.6 μM TAE684 or without (controls).…”
Section: Methodsmentioning
confidence: 99%
“…Sox10 plays a similar role in specification of both xanthophores and iridophores as well (Kelsh and Eisen, 2000;Dutton et al 2001). In the case of iridophores, as well as Sox10, the receptor tyrosine kinase Leukocyte tyrosine kinase (Ltk) plays a crucial role, with loss of function mutants lacking embryonic and adult iridophores, and constitutively activated Ltk signalling driving NCCs to adopt an iridophore fate (Lopes et al 2008;Rodrigues et al 2012;Fadeev et al 2016). We have shown that ltk expression appears to show two phases, one in early NC development which we propose represents a multipotent, chromatoblast-like progenitor, and a second in the definitive iridophore lineage (Lopes et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is clear that heterotypic interactions among all three types of pigment cells are necessary to generate the striped pattern (Frohnhöfer et al, 2013; Irion et al, 2014a; Singh et al, 2015), the outcome of these heterotypic interactions at the cellular level is not understood. In mutants where one type of pigment cells is absent [for example nacre/mitfa lacking melanophores (Lister et al, 1999), pfeffer/csf1ra lacking xanthophores (Parichy et al, 2000b) or shady/ltk lacking iridophores (Fadeev et al, 2016; Lopes et al, 2008)], only remnants of the normal stripe pattern are formed by the remaining two types of cells (see examples in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%